Peran Guru dalam Mengembangkan Nilai Agama dan Moral pada Anak Usia Dini di TK Pertiwi Pamekasan - Dina Rosfalia Nabila; Selfi Lailiyatul Iftitah (JCE (Journal of Childhood Education), 2025)
This research aimed to analyze the role of teachers in developing moral and religious values ​​in early childhood. The research method used was descriptive qualitative. Data collection and triangulation techniques were observation, interviews and documentation. The subjects of this study were three teachers at Pertiwi Pamekasan Kindergarten. The results of this study indicated: first, there are several roles of teachers in developing children's religious and moral values ​​at Pertiwi Pamekasan Kindergarten, namely; a) carrying out responsibilities to children to provide habits, b) motivators and advice providers, c) role models, providing examples of good behavior, d) supervisors, and e) assessors or observers of children's development achievements. Second, the supporting and inhibiting factors faced by teachers in developing religious and moral values ​​at Pertiwi Pamekasan Kindergarten. The supporting factors were; a) all teachers must be supporting factors for children b) support and cooperation between parents and teachers c) the school environment including facilities and infrastructure. Meanwhile, the inhibiting factors were non-conducive classes and some children who were less obedient. Third, solutions to the inhibiting factors faced by teachers in developing children's religious and moral values ​​at Pertiwi Kindergarten, Pamekasan, included: a) holding regular meetings or parenting programs once every three months b) using appropriate learning methods c) conducting evaluations of teachers and finding solutions to existing problems d) restoring children's focus through ice breaking.